PENGEMBANGAN APLIKASI RESERVASI PEMANCINGAN ONLINE BERBASIS ANDROID STUDI KASUS PEMANCINGAN KATINENUNG: DEVELOPMENT OF AN ANDROID-BASED ONLINE FISHING RESERVATION APPLICATION. KATINENUNG FISHING CASE STUDY - Hamdani Hamdani; Fadil Indra Sanjaya (LPPM Universitas Abdurrab, 2025)
Katineung Fishing Pond is a fishing venue that currently still uses a conventional booking process. Customers must come in person or call to reserve a spot, which often leads to uncertainty regarding availability and booking errors. Additionally, limited promotion has resulted in a lack of information about the fishing services available to the public. To address these issues, a more efficient and modern online reservation system is needed. This study utilizes the Rapid Application Development (RAD) method, which allows for rapid and iterative application development. The project aims to build an online reservation application that simplifies the booking process for customers and helps the management in handling reservation data. The application is developed using Dart programming language with the Flutter framework for the frontend and PHP with the Laravel framework for the backend, along with MySQL as the database. This system is expected to improve booking efficiency, provide real-time availability information, and enhance customer satisfaction. With this system, operational efficiency is anticipated to increase, customer experiences to improve, and the competitiveness of Katineung fishing pond to strengthen.